Touch the air - an event-driven framework for interactive environments - Neto, Almerindo Nascimento Rehem; Santos, Celso Alberto Saibel; Carvalho, Lucas Aragão de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Since the advent of Kinect, there has been an outbreak of applications that go beyond mouse and keyboard interfaces. Applications developers aim to enrich and re-imagine these interfaces using gesture and voice commands recognition for controlling some virtual and real world objects using a natural interaction mechanism. Aligned to this, there are problems to set a standard for these interfaces, plus a huge effort in performing simple tasks such as connecting sensors, processing data, recognizing gestures and running actions in real or virtual world. This paper proposes an extendable event-driven framework that improves the life cycle of designing and building interactive environments, making it possible to interact with both real and virtual environments.